(untitled) (Research, Society and Development, 2023)
The squamous cells carcinoma is considered the second neoplasm most commonly diagnosed in dogs oral cavity. The objetive this work consist in report a case of squamous cells carcinoma with location in the oral cavity in a canine, emphasizing in your clinic apresention and yours histopatologic and citologic aspects. Was answered a canine, male, 13 years old, volume increase complaint in oral cavity and ventral cervical region for trhee months, addition to difficulty swallowing. In the clinical examination, the presence of a nodule in the oral cavity was evidenced, affecting the gingiva, palate and glottis, its size could not be determined due to its extension and irregular appearance, flaccid consistency, poorly delimited and adhered. Fine needle cytology was performed with a diagnosis suggestive of squamous cell carcinoma. Cytological analysis of the increase on submandibular lymph node topography showed that it was a neoplastic extension. The patient was sedated for performing imaging tests to rule out lung metastasis and biopsy followed by histopathology of the oral neoplasm with diagnostic confirmation of grade III squamous cell carcinoma. Due to the neoplastic extension, unfavorable prognosis, low chemotherapy response and impossibility of surgical removal with a safety margin, the patient was euthanized. Also, we emphasize the importance of performing a cytological examination in neoplasms of the oral cavity of dogs, associated with histopathology to confirm the diagnosis and the possibility of more appropriate clinical and therapeutic management.